Saudi EFL University Students Readiness for Autonomous Language Learning - Mohammed, Abuelgasim (Colombian Applied Linguistics Journal, 2022)
Autonomous language learning (ALL) is considered a step to prepar students for their future. It is one aspect of learner – centered approach. Therefore, investigating students’ readiness for AL could be of paramount importance. This study aimed at revealing Saudi English major students’ readiness for ALL. More precisely, the study sought to identify the students’ view on their own responsibility and their teachers toward learning English, their ability to behave autonomously, and their actual practice of AL outside the classroom. A questionnaire was adopted to collect data. The participants were 105 students majoring in English language, College of Science & Humanities (CSH), Prince Sattam Bin Abdulaziz University (PSAU). Results of the study revealed a relation between the students’ own responsibility and their teachers for the process of learning English language. However, the students assigned more responsibility to their teachers. It was also found that the participants were not confident in their ability to behave autonomously when learning English. Finally, the results showed that the participants have not practiced, on their own, several activities given in the questionnaire outside the classroom. Generally, the participants were not ready for ALL. The study recommended that students’ awareness to the advantages of ALL should be raised.